Enhancing Students' Vocabulary Mastery through Assembler Edu Application Based on Augmented Reality of The Seventh Grade MTs Darul Mukhlisin - Zulvi, Maulana; Zulkarnain, Iskandar; Rangkuti, Linda Astuti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This research aims at enhancing students’ vocabulary mastery through Assembler Edu Application based on Augmented Reality. It was conducted by using Classroom Action Research that consisted in two cycles. Each cycle consisted of planning, action, observation and reflection. The subject of this research was the students of the seventh grade MTs. Darul Mukhlisin consisted of 30 students. The instruments of this research were observation, interview, test, documentation, and questionnaire. The technique of analyzing the data was done in two ways, namely descriptive technique and statistical technique. Descriptive technique was used to analyze qualitative data obtained from interview sheets, observation sheets, questionnaire sheets, and documentation. Meanwhile, statistical technique was used to analyze quantitative data obtained from students’ test result, both orientation test and post-test. The findings of this research were the mean score of students on the orientation test was only 80,6, then increased in the post-test cycle I to 90.1 and continued to increase until it reached 91.4 in the post-test cycle II. Then through the questionnaire in the conclusion that the students at the first time using the assembler edu application as many as (43.3%) or around 13 students were able to answer English vocabulary questions and then increased to (90%) or 27 students at the time of giving the second questionnaire. The number of students achieved the KKM score also increased. In the orientation test, there were only 8 (26.6%) students achieved the KKM score. In the post-test cycle I increased to 29 (96.6%) students, and in the post-test cycle II all students (100%) increased to reach and even exceed the KKM score. From the results of the qualitative and quantitative data analysis, it can be concluded that the Assembler Edu Application based on Augmented Reality significantly enhanced students’ vocabulary mastery.